Implementation of Counseling through Islamic Religious Courts in Resolving Polygamy Household Disputes - Pagar, Pagar; Khair, Nispul; Siregar, Fikri Bayu (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the implementation of counselees through Islamic religious courts in resolving polygamous household disputes (a case study at the Rantauprapat Islamic religious court, Labuhanbatu Regency in 2018-2021), especially about how it is planned, what are the steps, what are the inhibiting and supporting factors, and why the need for counselees at the Rantauprapat religious court. This study uses a qualitative method. This research takes place at the center of the Rantauprapat religious court. Data collection techniques using documentation, interviews and observations. The data analysis technique uses data collection, data reduction, data presentation and conclusions. The research informants here are the head of the religious court, judges, mediators, KUA and community leaders in Labuhanbatu. This research starts from the initial study from March to August 2021. The results showed that; 1) counselee planning at the religious court of Labuhan Batu Regency in reducing the number of polygamy disputes is carried out in two plans, namely based on service culture and based on transformative culture. 2) The counselee's steps at the Labuhan Batu Regency Religious Court in reducing the number of polygamy disputes are carried out in two steps, namely the Educational Step and the Consultative Step. 3) Inhibiting and supporting factors. The supporting factors are because of the facilities and infrastructure, the tools or instrumentals used, the understanding material about the importance of the sakinah family and the evaluation of technical implementation. Meanwhile, the inhibiting factors are the lack of awareness of some people to participate in the sakinah family program, less than optimal empowerment, less than optimal support from P3K, not yet optimal provision of constructive sakinah family development activities through the sakinah family festival.